Penyutradaraan Wayang Orang oleh: Sardana Mlaya Wibaksa - Sriyadi Sriyadi (Greget, 2010)
A director is a person who gives directions, instructions, and guidance to the performers or actors in aspects of their acting, dialogue, movements, and the way the dancers walk in a performance of traditional Javanese dance-drama, or wayang orang. The director is responsible for the entire process of a workâ€™s creation, up to the time of its performance. According to Sardana, a director must have the ability to cast actors or actresses in particular roles, according to their abilities as wayang orang performers.Keywords: Â Director and wayang orang.